Biochemical and cardiovascular predictors of PIMS risk in children after COVID-19 recovery =- the results of the LATE COVID Kids study. (14th October 2021) - Jatczak-Pawlik, I; Lewek, J; Czkwianianc, E; Zeman, K; Jankowski, P; Banach, M; ,
Abstract: Background: Unfortunately, the number of children with the pediatric inflammatory multisystem syndrome (PIMS) associated with previous coronavirus disease has been increasing significantly. Purpose: The aim of the present study was to characterize biochemical and cardiovascular predictors of PIMS risk in children recovered from COVID-19 based on the data from the LATE-COVID-Kids study (NCT04799444). Methods: 131 consecutive COVID-19 convalescents (mean age: 8.89±4.91; 67 boys and 64 girls) hospitalized for the clinical evaluation after the acute phase of the COVID-19 were classified into two groups related to symptoms: 29 children finally diagnosed with PIMS and 102 children with no-PIMS. All patients had confirmed coronavirus infection based on the positive results of nucleic acid test (RT-PCR - reverse transcriptase-polymerase chain), and they were serologically tested for antibodies against SARS-CoV-2. They had detailed laboratory testing, electrocardiography, and echocardiography. Results: The time from COVID-19 recovery was from 1 to 10 months (median 4.0 [3.00–5.00] months). Children with PIMS were significantly younger in comparison to those without (6.60±4.50 vs 9.50±4.80 years, respectively; p=0, 005). In comparison to non-PIMS group, children with PIMS had higher level of antithrombin III (111±7.23 vs. 104±10.9; p=0.0015), CK-MB (29.0 [18.5–36.0] vs. 21.0 [15.0–30.7]; p=0.03) and heart rate [HR]/min (100 [89.0–112] vs. 90.0 [79.0–100]; p=0.006) but lower PQ interval (120 [110–120] vs. 130 [120–140]; p=0.023) on admission to hospital. Moreover, the immunological parameters: IgA and neutrophils were lower in children with PIMS vs. no-PIMS (0.69 [0.47–0.85] vs. 1.19 [0.71–1.50]; p=0.0001 and 37.4%±13.3 vs. 43.0±11.6; p=0.0045, respectively), but lymphocytes were significantly higher (50.6±13.6 vs. 43.7±10.9; p=0.002). Some acid-base balance parameters were higher in children following PIMS vs. no-PIMS children group: pCO2 (41.30±5.70 vs. 45.0±7.00; p=0.019), pO2 (50.1 [38.4–59.7] vs. 37.8 [27.9–49.9]; p=0.007), and O2Sat (84.2 [69.3–90.6] vs. 64.2 [44.3–82.6]; p=0.004); however, concentration of HCO3- (23.6 [22.2–24.4] vs. 24.3 [22.8–26.2]; p=0.023) was lower in group of PIMS children. Conclusions: Based on our best knowledge, it is the first data on the possible predictors of PIMS risk in children recovered from COVID-19. We showed that children with PIMS have significantly higher levels of antithrombin III, CK-MB, HR, as well as lymphocytes, pCO2, pO2 and O2Sat on admission to hospital and lower levels of PQ interval, IgA, neutrophils and concentration of HCO3. We continue our research to confirm these results and to create the PIMS SCORE algorithm to allow prediction of children with the risk of PIMS occurrence after COVID-19 recovery. FUNDunding Acknowledgement: Type of funding sources: None.